Multi-objective optimization and algorithm improvement on thermal coupling of SOFC-GT-ORC integrated system. (August 2022) - Lei, Yuanting; Ye, Shuang; Xu, Yanyan; Kong, Chan; Xu, Changzhe; Chen, Yuting; Huang, Weiguang; Xiao, Hao
Highlights: A thermal coupling optimization model is proposed for reducing exergy destruction. The optimization variables include continuous, integer, and binary variables. An improved multi-objective particle swarm optimization algorithm is established. The results demonstrate the importance of thermal coupling optimization. The results prove the virtue of improved multi-objective optimization algorithm. Abstract: Optimizing thermal coupling of an integrated system and improving its energy cascade utilization (ECU) level are important ways to improve system performance. An integrated power generation system consisting of an anode recirculation internal reforming solid oxide fuel cell (ARIR-SOFC), a gas turbine (GT), an organic Rankine cycle (ORC) waste heat recovery system and a liquefied natural gas (LNG) supply system is established. Additionally, heat exchange network (HEN) subsystem formed by heat exchange streams is specially considered to further improve ECU level. Optimization model is proposed where HEN scheme is optimized simultaneously with operating parameters and working fluids of ORC. Because of the complexity of model, it is key to focus on the solution strategy. An adaptive improved multi-objective particle swarm optimization (IMOPSO) algorithm is established to improve diversity and accuracy of solutions. Finally, a case is solved and results show that HEN scheme plays an important role in system performance.